VR Based Media for Three-Dimensional (3D) Visualization in Chemical Laboratory - Mellyzar Mellyzar; Islami Fatwa; Isna Rezkia Lukman; Ucia Mahya Dewi; Ali Imron Pasaribu (Jurnal Penelitian Pendidikan IPA, 2024)
VR (VR) is a technology created with the aim of creating a three-dimensional (3DVR) simulated environment where users can observe and interact with the contents of that environment. This research aims to develop and assess the quality of a 3D-VR-Based Virtual Lab learning media. The development of learning media in this research uses the ADDIE development model. However, in this research, it is limited only to the development stage, namely validation by media experts and feasibility testing. Based on the validation results from each media validator, covering three aspects: audiovisual, software engineering, and instructional design, good results were obtained. Therefore, 3D-VR media developed is declared valid and feasible to be tested with learners.